Cognitive-linguistic scaffolding as a tool for activating argumentative writing skills in the process of teaching analytical chemistry in English language - Mitina, Tatyana; Afanasenkova, Irina; Bazarnova, Natalya; Shaikhova, Bakhyt; Oyamo, Maurice (International Journal of Innovative Research and Scientific Studies, 2025)
The influence of the cognitive-linguistic scaffolding method on the development of students' reasoned written speech in the context of studying analytical chemistry in English is considered. The study was based on the analysis of data obtained during the MSASC exam via quantitative, qualitative, and statistical methods of assessment. It reported a statistically significant improvement in argumentative skills, as confirmed by Wilcoxon tests. In particular, the proportion of students with a low level of argumentativeness decreased by 12.5%, and the number of students with a high level of argumentativeness increased by 31.25%. Correlation analysis revealed a tendency for the greatest improvement among students with an initially low level of preparation. The cognitive nature of scaffolding, its connection with Vygotsky's theory of the zone of proximal development, and Sweller's concept of cognitive load are discussed. The limitations of the study are identified, particularly the lack of a control group, which requires further longitudinal studies and comparative analysis of different scaffolding models. The practical significance of this study lies in the development of educational methods, the integration of digital scaffolding tools, and the improvement of academic writing training programs in the context of bilingual education.